BAGAIMANA PEMERINTAH DAERAH PROVINSI KALIMANTAN TIMUR PEDULI IKUT MEMBERANTAS FAHAM RADIKAL - Sudiyarti, Sudiyarti (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2018)
The aim of this research is to know the action of the regionalmeaningly the provincial government to prevent radicalism as well asterorism.The method of this research is qualitatif reseach by taking newsfrom library, such as daily local and national news paper and othermassmedia, observation and others. The location of the research is in EastKalimantan. The results of it are (1) The terorism attacks happenedeverywhere in the world 2) The regional governments are supposed not socare to the activities of radicalism and terorism group (3) There are twocategories whom the governments concerned have to pay attention, firtslythe citicenz who are being deported from the foreign countries, secondlythe former terorists who are becoming poor-group no money anymore forliving, they have nothing (4) Those who are involved the terorism aredifficult to come back to the society,(5) The nearest position with them arethe ragional gevernments.The suggestions are, (1) People all called to combat the terorismeverywhere in the world, (2) The regional governments have care andalert to the activities of radicalism and terorism group,firstly the citicenzwho are being deported from Middle East, secondly the former teroristswho are becoming poor group no money anymore for living, they havenothing. (3) Those who are involved the terorism are to be guided andhelped as usual citizens come back to the society, (5) The regionalgovernments which nearest position with them are the ragionalgevernments have to rehabilatate them.